lncRNA SNHG1 Promotes Basal Bladder Cancer Invasion via Interaction with PP2A Catalytic Subunit and Induction of Autophagy - Jiheng Xu; Rui Yang; Xiaohui Hua; Maowen Huang; Zhongxian Tian; Jingxia Li; Hoi Yun Lam; Guosong Jiang; Mitchell Cohen; Chuanshu Huang (Elsevier, 2020)
Although basal muscle-invasive bladder cancers (MIBCs) are predominant, are more aggressive, and have bad prognoses, molecular mechanisms underlying how basal MIBC formation/progression have been barely explored. In the present study, SNHG1, a long non-coding RNA, was shown to be expressed at higher levels in basal MIBC cells than in other types of bladder BC cells, and its presence could promote basal MIBC cell invasion. The results revealed that SNHG1 specifically induced MMP2 expression via increasing its transcription and mRNA stability. In one mechanism, SNHG1 directly bound with PP2A catalytic subunit (PP2A-c) to inhibit interactions of PP2A-c with c-Jun and then promoted c-Jun phosphorylation that, in turn, mediated MMP2 transcription. In another mechanism, SNHG1 markedly induced autophagy in the cells via induction of increases in the abundance of autophagy-related proteins. The latter initiated autophagy and further abolished miR-34a stability, which reduced overall miR-34a binding directly to the 3' UTR of MMP2 mRNA, thereby promoting MMP2 mRNA stabilization. These results provided novel insight into understanding the specific functions of SNHG1 in basal MIBC. Such findings may ultimately prove highly significant for the design/synthesis of new SNHG1-based compounds for the treatment of basal MIBC patients.